2019
DOI: 10.1093/nar/gkz291
|View full text |Cite
|
Sign up to set email alerts
|

Conformational tuning of a DNA-bound transcription factor

Abstract: Transcription factors are involved in many cellular processes that take place remote from their cognate DNA sequences. The efficiencies of these activities are thus in principle counteracted by high binding affinities of the factors to their cognate DNAs. Models such as facilitated diffusion or dissociation address this apparent contradiction. We show that the MYC associated transcription factor X (MAX) undergoes nanoscale conformational fluctuations in the DNA-bound state, which is consistent with facilitated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 36 publications
2
19
0
Order By: Relevance
“…Finally, in our earlier work we could show that MAX 2 ’s NTD undergoes substantial internal motions even when in the stable DNA-bound helical state. A comparison of the data 16 for MAX 2 bound to a DNA ligand with the results obtained here on DNA-free MAX 2 shows that the range of end-to-end distances sampled by MAX 2 ’s NTD is similarly broad (1.5–4.5 nm) in both the DNA-free and DNA-bound states. ( Figure 4 b,c shows DEER-derived distance distributions and form factors before (red) and after (blue) binding of DNA to MAX 2 for the R5C-R5C double mutant.)…”
mentioning
confidence: 64%
“…Finally, in our earlier work we could show that MAX 2 ’s NTD undergoes substantial internal motions even when in the stable DNA-bound helical state. A comparison of the data 16 for MAX 2 bound to a DNA ligand with the results obtained here on DNA-free MAX 2 shows that the range of end-to-end distances sampled by MAX 2 ’s NTD is similarly broad (1.5–4.5 nm) in both the DNA-free and DNA-bound states. ( Figure 4 b,c shows DEER-derived distance distributions and form factors before (red) and after (blue) binding of DNA to MAX 2 for the R5C-R5C double mutant.)…”
mentioning
confidence: 64%
“…In such an open state, the two BRs bind into the neighboring major and minor grooves on the DNA, respectively, with a distance in between (~33 Å) almost the length of a full DNA helical pitch. In a recent NMR integrated structural dynamics study which measured the Max-Max homodimer conformational fluctuations in association with DNA, it is found that the opening of the binding cleft varies in width by about 2-5 nm [40]. Such an opening of Max-Max may also apply for Myc-Max.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, approaches based on the site-specific introduction of paramagnetic labels could characterize the DNA-binding sites of (partially) disordered TFs [61] , [62] , [63] , [64] , [65] . These approaches employed the so-called paramagnetic relaxation enhancement (PRE) technique [66] .…”
Section: Combining Nmr and MD Simulationsmentioning
confidence: 99%
“…Recently, putting the combination of PRE-based relaxometry and MD simulations to use, the intrinsically disordered DNA-binding interface of the important transcription factor MAX (MYC-associated factor X) has been investigated [61] , [63] , [77] . It could be shown that its conformational space is not merely void of long-lived structural elements.…”
Section: Combining Nmr and MD Simulationsmentioning
confidence: 99%
See 1 more Smart Citation